A deformable shape memory scaffold material loaded with Mongolian medicine active ingredients and its preparation method and application

Through the deformable deformable shape memory scaffolding material loading the active ingredients of Mongolian medicine, the problem that existing bone graft materials cannot be customized and promote fracture healing is solved, and the regeneration of blood vessels and bone tissues under hypoxia is achieved and the gradual degradation of blood vessels and bone tissues is promoted under hypoxia conditions and gradually degraded effect.

CN119034007BActive Publication Date: 2025-02-21INNER MONGOLIA MEDICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411545106.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-21
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Existing bone graft materials cannot be customized according to the shape of the fracture, resulting in disorders in cell response and recognition after implantation and slow tissue healing, especially for patients with large irregular bone defects and osteoporosis.

Method used

Using the active ingredient of Mongolian medicine loaded with the deformation-deformable shape memory scaffolding material, the polyurethane scaffolding blank is injected into the polyurethane scaffolding blank by mixing apigenin-silver nanomedicine microspheres, nanosilver modified nanohydroxyapatite suspension and phase change material. Phase change is carried out to prepare scaffold materials that can promote regeneration of blood vessels and bone tissues and gradually degradation under hypoxia.

Benefits of technology

This material can stimulate the body to produce and recruit growth factors required for bone repair and angiogenesis, reduce the negative impact of reactive oxygen species on cells, promote the completion of bone repair, and be customized according to the shape of the fracture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119034007B_ABST
    Figure CN119034007B_ABST
Patent Text Reader

Abstract

The present invention provides a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients and a preparation method and application thereof, and relates to the technical field of composite materials. The preparation method of the deformable shape memory scaffold material loaded with Mongolian medicine active ingredients provided by the present invention comprises the following steps: mixing apigenin-silk fibroin nano drug-loaded microspheres, nano-silver modified nano-hydroxyapatite suspension and polyurethane material to obtain a mixture; molding the mixture to obtain a polyurethane scaffold blank; heating the mixture, injecting the obtained hot mixture into the polyurethane scaffold blank, performing phase change, and obtaining a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients. The deformable shape memory scaffold material loaded with Mongolian medicine active ingredients prepared by the present invention can stimulate the body to produce and recruit growth factors required for bone repair and angiogenesis, and reduce the negative impact of ROS on cells, thereby promoting the completion of bone repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients, and a preparation method and application thereof. Background Art

[0002] Clinically, defects are often caused by trauma, infection, tumors or developmental abnormalities. When the bone defect exceeds 1.5 to 2 times the diameter of the bone shaft or more than 1 / 10 of the length of the long bone, especially when the shape of the bone defect is extremely irregular, the natural repair capacity of the bone reaches its upper limit, and the probability of delayed healing of bone injury or nonunion increases significantly, greatly affecting the patient's quality of life and increasing the probability of disability. At present, autologous bone transplantation is an ideal method for large-segment bone repair in clinical practice, but its clinical application is limited by complications such as limited donors, donor site infection, and pain. Allogeneic bone transplantation is difficult to be widely used due to high rejection reactions and high infection risks. At present, bioinert materials such as alumina, stainless steel and polymethyl methacrylate are used as bone graft materials in clinical practice (NOORI A, ASHRAFI SJ, VAEZ-GHAEMI R, et al. A review of offibrin and fibrin composites for bone tissue engineering[J]. Internationaljournal of nanomedicine, 2017,19(10): 4937-4961.). However, these biomaterials cannot be customized according to the shape of the fracture, resulting in problems such as cell response and recognition disorders after implantation and slow tissue healing. The repair effect is not ideal, especially for large irregular bone defects and aging patients with osteoporosis, diabetes and other conditions with weak bone regeneration ability. The key problem of fracture healing is that the vascularization regeneration of bone tissue inside the implant has not been effectively solved.

[0003] Neovascularization in bone tissue is a dynamic process of developing new capillaries from existing capillaries or post-capillary veins, involving the participation of multiple cells, matrices and bioactive factors. The specific process includes: activation of endothelial cells and degradation of surrounding matrix, migration of endothelial cells, formation and proliferation of capillary buds. Neovascularization can promote the formation of granulation tissue, provide oxygen and nutrients to the injured area, and play an important role in bone repair. Before the completion of vascularization, the internal cells of large bone defect grafts often die due to hypoxia, which in turn triggers a negative inflammatory response, resulting in poor integration of the implant with the host bone tissue, and ultimately rejection. In short, vascular regeneration is a prerequisite for the repair of large bone injuries. It is not only a bridge for bone tissue nutrition and metabolism, but also a provider of bone regeneration microenvironment. The ideal large bone defect repair scaffold can be matched according to the different conditions of the fracture ends, construct a bionic microenvironment for optimal bone growth, and promote the regeneration of blood vessels and bone tissue under hypoxia. The scaffold itself is gradually degraded and absorbed to complete the purpose of repairing large bone defects. Therefore, improving the personalization of scaffolds and preparing large bone substitutes with functional vascular systems under hypoxic conditions are currently difficult problems that need to be solved urgently in the repair of large bone injuries.

[0004] Three-dimensional printing and bioprinting can imitate the complex structures of various organs according to predetermined heights and shapes, and prepare tissue structures that adapt to the size and shape of defects, which has extremely high application value in the field of regenerative medicine. 3D printed scaffolds used for bone tissue engineering are usually organic biomaterials such as gelatin, chitosan, hyaluronic acid, polycaprolactone, and inorganic materials such as hydroxyapatite, calcium phosphate, bioceramics, and bioactive glass (Liao Xinyu, Wang Fuke, Wang Guoliang. Progress and Challenges of Bone Tissue Engineering Scaffolds [J]. Chinese Journal of Tissue Engineering Research, 2021, 25(28): 4553-4560.). Although 3D printing has advantages in personalized customization, the vascularization of bone grafts is an important challenge in bone defect repair and a highly limiting factor in clinical regenerative medicine. When using 3D printed scaffolds to treat large bone defects, due to the slow vascularization process of the implant, the newly formed capillaries are essentially unable to meet the growth needs of the newly formed tissue or implanted cells, resulting in low cell viability and lack of integration with the host tissue in the central area of ​​the scaffold due to ischemia and hypoxia. At present, the common solution is to use biological ink containing cells and growth factors as scaffold materials, prefabricate vascular networks and vascularized tissue pedicles, and produce synergistic effects with proteins, growth factors and cells, and use different bioactive molecules to reproduce the in vivo environment, provide physical and chemical support for cell regulation and survival, and achieve the purpose of rapid vascularization of implants. However, the growth factor has a short action time, and excessive release may cause systemic toxic reactions; and the low oxygen supply environment in the defect area can lead to the accumulation of reactive oxygen species (ROS) inside the cells and induce cell apoptosis. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a deformable shape-memory scaffold material loaded with Mongolian medicine active ingredients, and a preparation method and application thereof. The deformable shape-memory scaffold material loaded with Mongolian medicine active ingredients prepared by the present invention can stimulate the body to produce and recruit growth factors required for bone repair and angiogenesis, reduce the negative impact of ROS on cells, and promote the completion of bone repair.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients, comprising the following steps:

[0008] The apigenin-silk fibroin nano drug-loaded microspheres, the nano-silver modified nano-hydroxyapatite suspension and the phase change material are mixed to obtain a mixture;

[0009] Molding the polyurethane material to obtain a polyurethane bracket blank;

[0010] The mixed material is heated, and the obtained hot mixed material is injected into the polyurethane stent blank to undergo phase change, thereby obtaining a deformable shape memory stent material loaded with Mongolian medicine active ingredients.

[0011] Preferably, the preparation method of the apigenin-silk fibroin nano-drug-loaded microspheres comprises: mixing a silk fibroin solution, apigenin, polyvinyl alcohol and ethanol to obtain a mixed solution; freezing the mixed solution, discarding the supernatant after thawing, and obtaining apigenin-silk fibroin nano-drug-loaded microspheres.

[0012] Preferably, the mass of apigenin in the apigenin-silk fibroin drug-loaded nanoparticles accounts for 0.1-20% of the mass of silk fibroin.

[0013] Preferably, the preparation method of the nano-silver modified nano-hydroxyapatite suspension comprises: mixing silver nitrate, water, nano-hydroxyapatite, isopropanol and glucose, and reacting to obtain the nano-silver modified nano-hydroxyapatite suspension;

[0014] The mass ratio of the silver nitrate to the nano-hydroxyapatite is 5-20:2-10.

[0015] Preferably, the phase change material comprises a gelatin aqueous solution; the concentration of the gelatin aqueous solution is 5-20wt%;

[0016] The mass of the apigenin-silk fibroin nano drug-loaded microspheres accounts for 5-30% of the mass of the phase change material.

[0017] Preferably, the temperature of the hot mix is ​​70-90°C.

[0018] Preferably, the forming comprises additive manufacturing.

[0019] Preferably, the molding comprises 3D printing.

[0020] The present invention provides a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients prepared by the preparation method described in the above technical scheme.

[0021] The present invention provides the use of the deformable shape memory scaffold material loaded with Mongolian medicine active ingredients described in the above technical solution in the preparation of bone scaffold materials.

[0022] The present invention provides a method for preparing a deformable shape memory stent material loaded with Mongolian medicine active ingredients. The present invention utilizes the advantages of traditional medicine, combines apigenin, an effective active ingredient in promoting angiogenesis in the Mongolian medicine blue spinulosa, with a deformable shape memory stent, and prepares a degradable, deformable shape memory pro-angiogenic stent containing pro-angiogenic active ingredients, so that the implant can stimulate the body to produce and recruit growth factors required for bone repair and angiogenesis, reduce the negative impact of ROS on cells, and promote the completion of bone repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the core-shell structure of apigenin-silk fibroin nanoparticles;

[0024] Figure 2 Transmission electron microscope image (left) and particle size distribution diagram (right) of silver nanoparticles;

[0025] Figure 3 Transmission electron microscopy image (left) and particle size distribution diagram (right) of nano-hydroxyapatite particles modified with nano-silver;

[0026] Figure 4 This is a scanning electron micrograph of the apigenin-silk fibroin nanoparticles prepared in Example 1;

[0027] Figure 5 The shape memory polyurethane prepared in Example 1 1 H NMR spectrum;

[0028] Figure 6 This is a thermogravimetric analysis diagram of the shape memory polyurethane prepared in Example 1;

[0029] Figure 7 This is a real picture of the 3D printed shape memory stent blank prepared in Example 1;

[0030] Figure 8 This is the overall actual picture (left) and the partial enlarged picture (right) of the deformable shape memory scaffold material loaded with Mongolian medicine active ingredients prepared by 3D printing technology before freezing in Example 1. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients, comprising the following steps:

[0032] The apigenin-silk fibroin nano drug-loaded microspheres, the nano-silver modified nano-hydroxyapatite suspension and the phase change material are mixed to obtain a mixture;

[0033] Molding the polyurethane material to obtain a polyurethane bracket blank;

[0034] The mixed material is heated, and the obtained hot mixed material is injected into the polyurethane stent blank to undergo phase change, thereby obtaining a deformable shape memory stent material loaded with Mongolian medicine active ingredients.

[0035] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0036] The invention mixes apigenin-silk fibroin nano drug-carrying microspheres, nano silver-modified nano hydroxyapatite suspension and phase change material to obtain a mixture.

[0037] In the present invention, the apigenin-silk fibroin nanoparticles have a core-shell structure ( Figure 1 As shown), the shell includes silk fibroin and polyvinyl alcohol, and the core includes apigenin. In the present invention, the mass of apigenin in the apigenin-silk fibroin nano-drug-loaded microspheres preferably accounts for 0.1-20% of the mass of silk fibroin, more preferably 0.5-15%, and further preferably 1-10%. The apigenin in Echinops cyanobacteria can promote angiogenesis under hypoxic conditions, reduce stress reactions and hypoxic damage caused by hypoxia, and promote smooth bone defect repair. In the present invention, the weight-average molecular weight of the polyvinyl alcohol is preferably 8000-20000, more preferably 10000-15000.

[0038] In the present invention, the method for preparing the apigenin-silk fibroin nano-drug-loaded microspheres preferably comprises the following steps: mixing a silk fibroin solution, apigenin, polyvinyl alcohol and ethanol, and performing self-assembly to obtain apigenin-silk fibroin nano-drug-loaded microspheres.

[0039] In the present invention, the concentration of the silk fibroin solution is preferably 1-100 mg / mL, more preferably 10-60 mg / mL, and further preferably 40 mg / mL. The present invention has no particular limitation on the preparation method of the silk fibroin solution, and any preparation method known to those skilled in the art can be used.

[0040] In a specific embodiment of the present invention, the method for preparing the silk fibroin solution preferably comprises: degumming natural mulberry silk to obtain silk; dissolving the silk in a solvent to obtain a mixed solution; and sequentially performing dialysis treatment and purification treatment on the mixed solution to obtain a silk fibroin solution. In the present invention, the degumming preferably comprises: mixing and boiling natural mulberry silk, sodium carbonate and boiling water. In the present invention, the mass ratio of the natural mulberry silk to sodium carbonate is preferably 1:0.5~1.5, more preferably 1:0.8~1. In the present invention, the boiling time is preferably 20~40min, more preferably 30min; the boiling is preferably carried out under stirring conditions. After the degumming, the present invention preferably further comprises washing the degummed silk with water and then drying to obtain silk. In the present invention, the solvent preferably includes lithium bromide solution or calcium chloride ternary solution; the concentration of the lithium bromide solution is preferably 8-12 mol / L, more preferably 9.3 mol / L; the composition of the calcium chloride ternary solution preferably includes calcium chloride, ethanol and water; the molar ratio of calcium chloride, ethanol and water is preferably 1:2:8. In the present invention, the dissolution temperature is preferably 50-70°C, more preferably 60°C; the dissolution time is preferably 3-5h, more preferably 4h. In the present invention, the dialysis treatment preferably includes water dialysis, and the molecular weight cutoff of the dialysis bag used in the dialysis treatment is preferably 3500Da-12000Da, more preferably 3500-5000Da; the dialysis time is preferably 2-4d, more preferably 3d; during the dialysis treatment, the water is preferably replaced every 2-4h (more preferably 3h); the water preferably includes deionized water. In the present invention, the purification preferably includes centrifugal separation, and the supernatant is a protein solution; the rotation speed of the centrifugal separation is preferably 8000~10000r / min, more preferably 9000r / min; the time of the centrifugal separation is preferably 20~40min, more preferably 30min; the temperature of the centrifugal separation is preferably 1~5°C, more preferably 4°C.

[0041] In the present invention, the source of apigenin is preferably Mongolian medicine Echinops cylindrica. The present invention has no special requirements on the method of extracting apigenin from Mongolian medicine Echinops cylindrica, and any extraction method known to those skilled in the art can be used.

[0042] In the present invention, the preparation method of apigenin preferably includes: mixing Echinops blue powder (dried) with ethanol aqueous solution to extract and obtain an extract; concentrating the extract to obtain an extract; freeze-drying the extract to obtain a freeze-dried powder; re-dissolving the freeze-dried powder, and separating the obtained freeze-dried powder solution by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin.

[0043] The present invention mixes the blue echinops powder (dried) with an ethanol aqueous solution for extraction to obtain an extract. In the present invention, the volume fraction of ethanol in the ethanol aqueous solution is preferably 30-100%, more preferably 50-75%; the amount ratio of the blue echinops powder (dry weight) to the ethanol solution is preferably 1kg:1-10L, more preferably 1kg:2-5L. In the present invention, the extraction temperature is preferably 25-80°C, more preferably 50-60°C; the extraction time is preferably 6-20 h, more preferably 12-20 h; the extraction is preferably carried out under stirring conditions.

[0044] After the extraction is completed, the present invention preferably further comprises performing solid-liquid separation on the obtained extraction system to obtain an extract. The present invention has no particular limitation on the solid-liquid separation, and a solid-liquid separation method well known to those skilled in the art can be used, such as filtration; the purpose of the solid-liquid separation is to remove residues.

[0045] After obtaining the extract, the present invention concentrates the extract to obtain an extract. In the present invention, the concentration preferably includes rotary evaporation; the rotary evaporation temperature is preferably 25-80°C, more preferably 60-80°C; the rotary evaporation time is preferably 2-10 hours, more preferably 4-5 hours.

[0046] After obtaining the extract, the present invention freeze-dries the extract to obtain freeze-dried powder. The present invention has no special limitation on the freeze-drying, as long as the solvent in the extract can be completely removed.

[0047] After obtaining the freeze-dried powder, the present invention re-dissolves the freeze-dried powder, and separates the obtained freeze-dried powder solution by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin. In the present invention, the concentration of the freeze-dried powder solution is preferably 20-100 mg / mL, more preferably 50-80 mg / mL; the solvent in the freeze-dried powder solution preferably includes a lower alcohol aqueous solution, and the volume fraction of the lower alcohol in the lower alcohol aqueous solution is preferably 20-100%, more preferably 30-90%, and further preferably 40-50%; the lower alcohol preferably includes methanol and / or ethanol. In the present invention, the conditions for high performance liquid chromatography-tandem mass spectrometry separation preferably include: high performance liquid chromatography-tandem mass spectrometry separation conditions: using Vanquish UHPLC (Thermo Scientific, Waltham, MA) ultra-high performance liquid chromatography system combined with ACQUITY UPLC HSS T3 (2.1 mm × 100 mm, 1.8 µm) chromatographic column for separation, column temperature is 35°C; flow rate is 0.3 mL / min; mobile phase: mobile phase A is 0.1 v / v% formic acid aqueous solution, mobile phase B is 0.1 v / v% formic acid-acetonitrile; elution mode is gradient elution, and the gradient elution program is shown in Table 1. The Q-Exactive HFX mass spectrometer was used to collect the primary and secondary spectra of the samples. The Q-Exactive HFX mass spectrometer sample was connected to the UHPLC system. The electrospray ionization (ESI) positive and negative ion modes were used for mass spectrometry acquisition. The spray voltage was 3800V (ESI+) / 3500V (ESI-), the sheath gas pressure was 45arb, the auxiliary gas pressure was 20arb, the ion transfer tube temperature was 320℃, and the nebulization temperature was 350℃. The detection mode was full scan / data-dependent secondary scan (Full-MS / dd-MS2) mode. The primary and secondary resolutions were 60000 and 15000, respectively. The top 10 MS1 ions obtained MS / MS spectra and collision energies (CEs). The step normalization energy levels were 20, 40, and 60; the primary mass-to-charge ratio scanning range was 90~1300. 2 μL of EC-sp solution was accurately aspirated and analyzed by LC-MS injection. The EC-sp sample was injected 5 times.

[0048] Table 1 Gradient elution program

[0049]

[0050] In the present invention, the apigenin is preferably used in the form of an apigenin solution, and the concentration of the apigenin solution is preferably 10 μmol / L to 10 mmol / L, more preferably 1 to 5 mmol / L, and further preferably 2 mmol / L. In the present invention, the solvent in the apigenin solution is preferably anhydrous ethanol.

[0051] In the present invention, apigenin has anti-inflammatory and antioxidant effects, can accelerate the rapid repair of the wound site; and can also effectively promote blood vessel regeneration.

[0052] In the present invention, the polyvinyl alcohol is preferably used in the form of a polyvinyl alcohol aqueous solution. The solvent in the polyvinyl alcohol aqueous solution is preferably water. The concentration of the polyvinyl alcohol aqueous solution is preferably 0.1 to 5 wt %, more preferably 1 to 2 wt %.

[0053] In the present invention, the mixing of the silk fibroin solution, apigenin, polyvinyl alcohol and ethanol preferably comprises: mixing the silk fibroin solution and the apigenin solution, adding a polyvinyl alcohol aqueous solution and ethanol. In the present invention, the ratio of the total mass of the silk fibroin solution and the apigenin solution, the mass of the polyvinyl alcohol aqueous solution and the mass of ethanol is preferably 10:0.1~5:1~3, more preferably 10:0.15~1:1~2, and further preferably 10:0.2:1. In the present invention, the concentration of the polyvinyl alcohol aqueous solution is preferably 0.1~5 wt%, more preferably 1~2 wt%. In the present invention, the ethanol is preferably anhydrous ethanol.

[0054] In the present invention, the self-assembly preferably includes freezing and thawing in sequence. In the present invention, the freezing temperature is preferably -60 to 25°C, more preferably -20°C; the freezing time is preferably 12 to 72 hours, more preferably 36 to 48 hours.

[0055] After the thawing is completed, the present invention preferably further comprises centrifuging the obtained thawing system, washing the obtained solid components and then drying them to obtain apigenin-silk fibroin nanoparticles. In the present invention, the speed of the centrifugation is preferably 8000-18000 r / min, more preferably 10000-12000 r / min; the time of the centrifugation is preferably 10-120 min, more preferably 30-100 min. In the present invention, the washing preferably comprises washing with deionized water 2-3 times. In the present invention, the drying preferably comprises freeze-drying, and the freeze-drying temperature is preferably -60-25°C, more preferably -20°C; the freeze-drying time is preferably 48-72 h.

[0056] In the present invention, the apigenin-silk fibroin nano-drug-loaded microspheres are preferably used in the form of apigenin-silk fibroin nano-drug-loaded microsphere suspension, and the concentration of the apigenin-silk fibroin nano-drug-loaded microsphere suspension is preferably 0.1~50 mg / mL, more preferably 5~30 mg / mL, and further preferably 10~20 mg / mL.

[0057] In the present invention, the structure of the nano-silver modified nano-hydroxyapatite in the nano-silver modified nano-hydroxyapatite suspension is a nano-scale rod-like structure. In the present invention, the preparation method of the nano-silver modified nano-hydroxyapatite suspension preferably comprises: mixing silver nitrate, water, nano-hydroxyapatite, isopropanol and glucose, and performing an oxidation-reduction reaction to obtain the nano-silver modified nano-hydroxyapatite suspension.

[0058] In the present invention, the mass ratio of the silver nitrate to the nano-hydroxyapatite is preferably 5-30:2-20, more preferably 5-20:5-10. In the present invention, the dosage ratio of the nano-hydroxyapatite to isopropanol is preferably 10-20 mg:1 mL, more preferably 10-15 mg:1 mL; the isopropanol acts as a dispersant. In the present invention, the mass ratio of the silver nitrate to the glucose is preferably 5-30:10-100, more preferably 5-20:50. In the present invention, the glucose is preferably in powder form.

[0059] In the present invention, the mixing of silver nitrate, water, nano-hydroxyapatite, isopropanol and glucose preferably includes: mixing silver nitrate and part of the water to obtain a silver nitrate solution; mixing glucose and the remaining water to obtain a glucose solution; heating the silver nitrate solution to the temperature of the reduction reaction, and sequentially adding nano-hydroxyapatite, isopropanol and glucose solution. In the present invention, the concentration of the silver nitrate solution is preferably 5-50 mg / mL, more preferably 10-40 mg / mL, and further preferably 20-30 mg / mL. In the present invention, the concentration of the glucose solution is preferably 50-150 mg / mL, more preferably 80-120 mg / mL, and further preferably 100 mg / mL.

[0060] In the present invention, the temperature of the redox reaction is preferably 25-90°C, more preferably 50-80°C; the time of the redox reaction is preferably 10-120 min, more preferably 30-60 min; during the redox reaction, glucose reduces silver nitrate to obtain silver element (nanosilver).

[0061] The present invention preferably washes the obtained redox reaction system after the redox reaction to obtain a nano-silver modified nano-hydroxyapatite suspension. In the present invention, the washing solution used for the washing is preferably deionized water, and the number of washings is preferably 1 to 4 times, more preferably 2 to 3 times. In the present invention, the concentration of the nano-silver modified nano-hydroxyapatite suspension is preferably 0.1 to 50 mg / mL, more preferably 10 to 40 mg / mL, and further preferably 20 mg / mL.

[0062] In the present invention, the phase change material preferably includes a gelatin aqueous solution, and the concentration of the gelatin aqueous solution is preferably 5~20wt%, more preferably 10~15wt%; the mass of the phase change material preferably accounts for 5~30% of the mass of the apigenin-silk fibroin nano-drug-loaded microspheres, more preferably 10~20%, and further preferably 15~20%.

[0063] In the present invention, the temperature for mixing the apigenin-silk fibroin nano-drug-loaded microspheres, the nano-silver modified nano-hydroxyapatite suspension and the phase change material is preferably 60-100°C, more preferably 70-90°C, and further preferably 80°C; the present invention has no special limitation on the mixing time, as long as the raw materials can be mixed evenly.

[0064] The invention molds the polyurethane material to obtain the polyurethane bracket blank.

[0065] In the present invention, the polyurethane material preferably includes degradable polyurethane, and more preferably includes linear degradable shape memory polyurethane.

[0066] In the present invention, the molding preferably includes additive manufacturing, and specifically preferably 3D printing. In the present invention, the conditions of the 3D printing preferably include: the barrel temperature is set to 80~200℃, more preferably 100~145℃; the platform temperature is set to -20~25℃, more preferably 4~10℃; the extrusion pressure is 0.1~1 MPa, more preferably 0.5~0.8MPa; the extrusion speed is 0.01~1 mm / s, more preferably 0.1~0.5 mm / s; the wire is advanced for 30~60 ms, more preferably 40~50 ms; the wire is closed in advance for 1~10ms, more preferably 1~5 ms, and the broken wire is raised by 10~20 mm, more preferably 15 mm; the printing parameters preferably include: the printing model is cylindrical, linear filling is used, the filling spacing is 0.1~5 mm, more preferably 1~2 mm; the number of rotations is 80~100 times, more preferably 88~95 times; the rotation angle is 90°.

[0067] The present invention adopts 3D bioprinting technology to imitate the complex structure of various bone defects according to predetermined height and shape, prepares tissue structure that adapts to the size and shape of the defect, and introduces deformable shape memory material to increase the mechanical response between the scaffold and the defect site after implantation, thereby accelerating the healing of bone defects.

[0068] After obtaining the mixture and the polyurethane bracket blank, the present invention heats the mixture, injects the obtained hot mixture into the polyurethane bracket blank, performs phase change, and obtains a deformable shape memory bracket material loaded with Mongolian medicine active ingredients.

[0069] In the present invention, the temperature of the hot mix is ​​preferably 70-90°C, more preferably 80°C.

[0070] In the present invention, the phase change preferably includes natural cooling to room temperature. The present invention fills the polyurethane stent blank with apigenin-silk fibroin nano drug-loaded microspheres, nano silver-modified nano hydroxyapatite and phase change material through phase change.

[0071] After the phase change is completed, the present invention preferably further comprises: freeze-drying the obtained phase-changed material to obtain a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients. In the present invention, the freezing preferably comprises freezing at -20°C for 12 h, and then freeze-drying in a freeze dryer for 48 h.

[0072] The present invention provides a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients prepared by the preparation method described in the above technical solution. In the present invention, the deformable shape memory scaffold material loaded with Mongolian medicine active ingredients comprises a polyurethane scaffold blank, a mixture of apigenin-silk fibroin nano drug-loaded microspheres, nano-silver modified nano-hydroxyapatite and phase change material filled in the pores of the polyurethane scaffold blank.

[0073] The present invention provides the application of the deformable shape memory scaffold material loaded with Mongolian medicine active ingredients described in the above technical solution in the preparation of bone scaffold materials. The present invention combines Mongolian medicine with 3D printing technology, uses network pharmacology to analyze the possible effective active ingredients in Mongolian medicine and conducts in vitro verification, and then uses 3D printing technology to prepare a degradable pro-angiogenic scaffold containing pro-angiogenic active ingredients, explores its application potential as a bone scaffold material, and provides new treatment ideas and clinical therapies for the repair and reconstruction of large bone defects.

[0074] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0075] Example 1

[0076] Preparation of apigenin-silk fibroin nanoparticles:

[0077] 1 kg of dried blue echinops powder was mixed with 2 L of 75% ethanol aqueous solution, heated to 60°C for mechanical stirring, extracted for 12 h, filtered, and the residue was removed. The obtained extract was rotary evaporated at 80°C for 4 h to evaporate the ethanol to obtain a drug extract, which was frozen at -20°C for 12 h and freeze-dried in a freeze dryer to obtain a freeze-dried powder. The freeze-dried powder was dissolved in a 40v / v% methanol aqueous solution, vortexed for 30 s, centrifuged at 16000 g and 4°C for 15 min, and the supernatant was a freeze-dried powder solution. The freeze-dried powder solution was separated by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin. The solid-liquid ratio of the freeze-dried powder to the methanol aqueous solution was 20 mg: 0.3 mL.

[0078] HPLC-MS / MS separation conditions: Vanquish UHPLC (Thermo Scientific, Waltham, MA) ultra-high performance liquid chromatography system combined with ACQUITY UPLC HSS T3 (2.1 mm × 100 mm, 1.8 µm) column was used for separation. The column temperature was 35 °C. The flow rate was 0.3 mL / min. The mobile phases were: mobile phase A was 0.1 v / v% formic acid in water, and mobile phase B was 0.1 v / v% formic acid-acetonitrile. The elution mode was gradient elution. The gradient elution program is shown in Table 1. The Q-Exactive HFX mass spectrometer was used to collect the primary and secondary spectra of the samples. The Q-Exactive HFX mass spectrometer sample was connected to the UHPLC system. The electrospray ionization (ESI) positive and negative ion modes were used for mass spectrometry acquisition. The spray voltage was 3800V (ESI+) / 3500V (ESI-), the sheath gas pressure was 45arb, the auxiliary gas pressure was 20arb, the ion transfer tube temperature was 320℃, and the nebulization temperature was 350℃. The detection mode was full scan / data-dependent secondary scan (Full-MS / dd-MS2) mode. The primary and secondary resolutions were 60000 and 15000, respectively. The top 10 MS1 ions obtained MS / MS spectra and collision energies (CEs). The step normalization energy levels were 20, 40, and 60; the primary mass-to-charge ratio scanning range was 90~1300. 2 μL of EC-sp solution was accurately aspirated and analyzed by LC-MS injection. The EC-sp sample was injected 5 times.

[0079] 2 L of deionized water was added to a water bath, heated to 100 °C, and then 4.24 g of anhydrous sodium carbonate and 5 g of natural mulberry silk were added. The mixture was boiled for 30 min to remove the sericin in the natural silk thread, and stirred at intervals during the heating process. The de-sericin-free silk was repeatedly rinsed with deionized water and dried in an oven at 60 °C to obtain silk. According to the ratio of silk to lithium bromide solution of 27 g:100 mL, 9.3 mol / L lithium bromide solution was added to the silk, and the silk was sealed with plastic wrap and pierced with holes. The silk was dried at 60 °C for 4 h. The obtained silk solution was placed in a dialysis bag (with a molecular weight cutoff of 3500 Da), sealed at both ends, and dialyzed in deionized water for 3 d. The deionized water was replaced every 3 h during the dialysis process. The dialyzed silk fibroin solution was divided into 50 mL centrifuge tubes and centrifuged at a speed of 9000 r / min, a time of 30 min, and a temperature of 4 The mixture was centrifuged at ℃, the lower precipitate was discarded, the supernatant was collected to obtain a silk fibroin solution, and the solution was stored in a 4℃ refrigerator. The concentration of the silk fibroin solution was detected by a BCA total protein kit, and the concentration of the silk fibroin solution was 40 mg / mL.

[0080] Polyvinyl alcohol (PVA) with a molecular weight of 20,000 was placed in deionized water, heated in a water bath at 95° C., and stirred until completely dissolved to obtain a 2 wt % polyvinyl alcohol aqueous solution.

[0081] The self-assembly method was used to prepare apigenin silk fibroin drug-loaded nanospheres. A 40 mg / mL silk fibroin solution and a 100 μM apigenin ethanol solution were mixed at a mass ratio of 10:1 to obtain a silk fibroin-apigenin mixed solution, and a 2 wt% PVA aqueous solution and anhydrous ethanol were added and mixed. The mixture was frozen at -20 °C for 48 h, thawed, centrifuged (12000 r / min, 30 min), the supernatant was discarded, the precipitate was collected, washed with deionized water 3 times, and freeze-dried at -20 °C to obtain apigenin silk fibroin drug-loaded nanospheres. The mass ratio of PVA to anhydrous ethanol in the silk fibroin-apigenin mixed solution and the PVA aqueous solution was 10:2:1.

[0082] Preparation of nano-silver modified nano-hydroxyapatite suspension:

[0083] Dissolve 20 mg of silver nitrate in 10 mL of deionized water and stir magnetically for 30 min; heat to 80°C, add 10 mg of nano-hydroxyapatite, continue stirring, add 1 mL of isopropanol, continue stirring for 10 min to obtain a mixed solution; dissolve 50 mg of glucose powder in 1 mL of deionized water, add to the mixed solution after it is fully dissolved, continue stirring for 60 min, wash with deionized water twice, and obtain a nano-silver modified nano-hydroxyapatite suspension with a concentration of 20 mg / mL.

[0084] Preparation of shape memory polyurethane:

[0085] Shape memory polyurethane materials were prepared according to the literature "Synthesis and characterization of biodegradable linear shape memory polyurethanes with high mechanical performance by incorporating novel long chain diisocyanates". The shape memory polyurethane to be prepared was tested using a nuclear magnetic resonance spectrometer (model: AVANCE500). 1 H NMR spectrum, such as Figure 5 As shown, the absorption peaks at σ = 7.3, 5.2, 3.7 and 0.75 ppm are consistent with those reported in the literature.

[0086] Preparation of deformable shape memory scaffold blank:

[0087] The shape memory polyurethane was placed in a barrel and 3D printed into a blank at 145℃. A 145℃ temperature printing nozzle was selected to complete the barrel loading. It was installed on the robotic arm of the 3D bioprinter, the nozzle temperature was set to 145℃, the platform temperature was set to 21℃, the extrusion pressure was 0.8 MPa, the extrusion speed was 0.1 mm / s, the filament was advanced by 50 ms, the filament was closed in advance by 1 ms, and the broken filament was raised by 15 mm. The printing parameters were set as follows: the printing model was cylindrical, linear filling was used, the filling spacing was 1 mm, the number of rotations was 88 times, and the rotation angle was 90°. The polyurethane scaffold blank was obtained by printing.

[0088] Preparation of deformable shape memory scaffold materials loaded with Mongolian medicine active ingredients by phase change:

[0089] 0.2 g of the apigenin-silk fibroin nano-drug-loaded microspheres, 0.1 g of the nano-silver modified nano-hydroxyapatite suspension and 1 g of a 10 wt% gelatin aqueous solution were mixed and heated to 80°C. The resulting hot mixture was injected into a polyurethane scaffold blank, naturally cooled to room temperature, frozen at -20°C for 12 h, and then freeze-dried in a freeze dryer for 48 h to obtain a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients.

[0090] Example 2

[0091] The preparation method is basically the same as that of Example 1, except that:

[0092] The preparation method of silk fibroin solution was adjusted as follows: calcium chloride, anhydrous ethanol and deionized water were prepared into a mixed solution at a molar ratio of 1:2:8 to obtain calcium chloride ternary solution; 2 L of deionized water was added to a water bath, heated to 100 °C, 4.24 g of anhydrous sodium carbonate and 5 g of natural mulberry silk were added, and the mixture was boiled for 30 min to remove the sericin in the natural silk thread, and stirred at intervals during the heating process; the degummed silk was repeatedly rinsed with deionized water and then dried in an oven at 60 °C; the mass of silk was weighed, and the calcium chloride ternary solution was added to the silk at a ratio of 1 g:15 mL of silk to the calcium chloride ternary solution, the silk was sealed with plastic wrap and pierced, and heated in a water bath at 80 °C for 1 h; the silk solution was placed in a dialysis bag (dialysis bag with a molecular weight cutoff of 3500), both ends were sealed, and the silk was dialyzed in deionized water for 3 d, and the dialysis process was repeated every 3-4 h. The deionized water was replaced once; the dialyzed silk fibroin solution was divided into 50 mL centrifuge tubes and centrifuged at a speed of 9000 g / min, a time of 30 min, and a temperature of 4 °C. The lower precipitate was discarded, and the supernatant was collected and stored in a 4 °C refrigerator; the concentration of the silk fibroin solution was measured by the BCA method, and a silk fibroin solution with a concentration of 40 mg / mL was prepared according to the obtained silk fibroin solution concentration.

[0093] Test Case

[0094] Preparation of nanosilver solution

[0095] Weigh 20 mg of silver nitrate and dissolve it in 10 mL of deionized water. Stir it magnetically for 30 min. Heat it to 80°C, add 1 mL of isopropanol, and continue stirring for 10 min to obtain a mixed solution. Dissolve 50 mg of glucose powder in 1 mL of deionized water, add the glucose powder solution to the mixed solution, continue stirring for 60 min, and wash it with deionized water twice to obtain a nanosilver solution for later use. Figure 2 The transmission electron microscope image (left) and particle size distribution diagram (right) of nanosilver particles. The particle size distribution of nanosilver particles is between 30 and 150 nm.

[0096] Preparation of Nano-Silver Modified Nano-Hydroxyapatite Suspension

[0097] Weigh 20 mg of silver nitrate and dissolve it in 10 mL of deionized water. Stir magnetically for 30 min. Heat to 80 °C, add 1 mL of isopropanol, and continue stirring for 10 min to obtain a mixed solution. Add 100 mg of nanohydroxyapatite to the mixed solution and continue magnetic stirring for 2 h. Dissolve 50 mg of glucose powder in 1 mL of deionized water, add the glucose powder solution to the mixed solution, continue stirring for 60 min, wash with deionized water twice, and obtain a nanosilver-modified nanohydroxyapatite suspension, which is dried for later use. Figure 3The transmission electron microscope image (left) and particle size distribution diagram (right) of nano-silver modified nano-hydroxyapatite particles show that the particle size distribution of nano-silver particles is between 80 and 400 nm.

[0098] The apigenin silk fibroin drug-loaded nano-microspheres prepared in Example 1 were sprayed with gold and observed using a scanning electron microscope. Figure 4 As shown, from the topological structure of the apigenin silk protein drug-loaded nanoparticles, it can be seen that the apigenin silk protein drug-loaded nanoparticles are spherical with a diameter between 50 and 500 nm.

[0099] Thermogravimetric analysis (TGA) and DSC test of shape memory polyurethane material: The DSC test was conducted on a DSC-Q100 differential scanning calorimeter from TA Instruments, USA, and the blank reference was an aluminum crucible. During the test, the sample was first heated from 20°C to 180°C, kept isothermal for 3 minutes, then cooled to -10°C, kept isothermal for 3 minutes, and finally heated to 150°C again. The heating or cooling rate was 10°C / min, the test atmosphere was N2, and the sample glass transition temperature (Tg) was based on the second temperature scan curve. Figure 6 As shown, the glass transition temperature of the shape memory polyurethane material is 60°C.

[0100] Figure 7 This is a real picture of the shape memory stent blank prepared by 3D printing technology in Example 1. It can be seen that the stent has a porous structure.

[0101] Figure 8 This is a physical picture of the deformable shape memory scaffold material loaded with Mongolian medicine active ingredients before freezing prepared by 3D printing technology in Example 1. It can be seen that the porous structure of the scaffold is filled with a mixed solution of apigenin-silk fibroin nano-drug-loaded microspheres, nano-silver modified nano-hydroxyapatite suspension and 10wt% gelatin aqueous solution.

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a deformable shape memory scaffold material loaded with Mongolian medicine active ingredients, comprising the following steps: The apigenin-silk fibroin nano drug-loaded microspheres, the nano-silver modified nano-hydroxyapatite suspension and the phase change material are mixed to obtain a mixture; in the preparation process of the nano-silver modified nano-hydroxyapatite suspension, the mass ratio of silver nitrate to nano-hydroxyapatite is 5-20:2-10; Molding the polyurethane material to obtain a polyurethane bracket blank; the molding includes 3D printing; The mixed material is heated, and the obtained hot mixed material is injected into the polyurethane stent blank to undergo phase change, thereby obtaining a deformable shape memory stent material loaded with Mongolian medicine active ingredients; the phase change material comprises a gelatin aqueous solution; the concentration of the gelatin aqueous solution is 5-20wt%; the mass of the apigenin-silk fibroin nano drug-loaded microspheres accounts for 5-30% of the mass of the phase change material; The preparation method of the apigenin-silk fibroin nano drug-loaded microspheres comprises: mixing a silk fibroin solution, apigenin, polyvinyl alcohol and ethanol to obtain a mixed solution; Freezing the mixed solution, discarding the supernatant after thawing, and obtaining apigenin-silk fibroin nano drug-loaded microspheres; The mass of apigenin in the apigenin-silk fibroin nano drug-loaded microspheres accounts for 0.1-20% of the mass of the silk fibroin.

2. The preparation method according to claim 1, characterized in that: The preparation method of the nano-silver modified nano-hydroxyapatite suspension comprises: mixing silver nitrate, water, nano-hydroxyapatite, isopropanol and glucose, and reacting to obtain the nano-silver modified nano-hydroxyapatite suspension.

3. The preparation method according to claim 1 or 2, wherein the temperature of the hot mix is ​​70-90°C.

4. The preparation method according to claim 1, characterized in that: The forming includes additive manufacturing.

5. The deformable shape-memory scaffold material loaded with Mongolian medicine active ingredients prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the deformable shape memory scaffold material loaded with Mongolian medicine active ingredients as described in claim 5 in the preparation of bone scaffold materials.

Citation Information

Patent Citations

  • Preparation of modified whey protein and application of modified whey protein in embedding apigenin

    CN117770347A

  • ID2018S01062A